Cultural Guidelines for Commercial Production of Interiorscape Dieffenbachia - Jianjun Chen; Dennis B. McConnell; Richard J. Henny; Kelly C. Everitt (EDIS)
This article describes common species and cultivars in the foliage plant industry, provides guidelines for their culture and interior use, and lists physiological problems that may be encountered during production and interiorscape use. This document is ENH880, one of a series of the Environmental Horticulture Department, Institute of Food and Agricultural Sciences, University of Florida. First published: March 2003.